ANTROPOLOGIA SEMÍTICA. UMA ANÁLISE EXEGÉTICA DA PERÍCOPE DE DT 6,1-9, COM APROXIMAÇÃO AO VOCÁBULO LEV. - Fábris, Rogério de (2014)
This research aims to research the word lev in the passage from Deuteronomy 6,1-9. This word is also used in various parts of the Old Testament. Thus the research also suggests a set of this use in view of various authors. The first chapter presents the blocks that constitute the frame of the book of Deuteronomy with the aim of identifying where the larger context is the pericope of Dt 6,1-9. In the second chapter we start from an exegetical analysis of the pericope highlighting the various aspects of language , such as writing style, literary genre, and content analysis. This part also contains a detailed analysis of the underlying text production realities, as historical seat, social, political and ideological. The third chapter presents the broad semantic field of the word lev in the Old Testament from the perspective of several authors. Such delineation aims to explore the polysemy of the word, and thus neutralize it, seeking the best sense of the word for the pericope of Dt 6,1-9.